Pendidikan bagi Anak Jalanan (Analisis Sosiologis Anak Jalanan di Desa Sosial Kaligelis Kudus) (THUFULA, 2014)
Education is very important in human life, especially children, as thesuccessor generation of people. The phenomenon of street children in the Holycity is not much different in other big cities in Indonesia. Activities of childrenon the streets are as beggars and buskers. On average, they are still listed asstudents in formal education, although some of them took the decision to getout of the formal education. The author tries to analyze the phenomenon withthe sociological approach, namely dramartugi theory, action and motivationdeveloped by David McClelland